Reconciliation: The theological challenge - Martin, SW (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
This paper argues that reconciliation is the Christian theological response to the challenge presented by a world of atrocities. While commonly articulated as adoctrine, reconciliation is primarily a narrative enacted through liturgy within Christian worship. This liturgy shapes a Christian response to a broken world, but is also provoked and challenged by that world. Within this movement, the church confesses that its practices of reconciliation are both incomplete and anticipatory. And yet these practices participate in the fullness of reconciliation made visible at the coming of the Kingdom. Anticipating this fullness allows Christian theology to articulate parables of reconciliation, and one example of this is South Africa’s own Truth and Reconciliation Commission. The paper concludes with a reflection on what “the parable of the TRC” says back to the church.